Response to Jennifer Lehmann's Reflections on Out-of-Home Care. (8th December 2015) - Broadley, Karen; Hunt, Susan; Goddard, Chris
Abstract : Jennifer Lehmann, in her reflections on out-of-home care (OOHC) in the preceding paper, offers an important contribution to this special issue of Children Australia (Lehmann, 2015 ). We are honoured to be involved and to provide this response.